Environmental problems are sidelined: issues raised during the KRI 2024 general election - Abdulrahman, Salam Abdulqadir (Technium Social Sciences Journal, 2025)
The Kurdistan Region of Iraq’s (KRI) 2024 general election focused primarily on political, social, and administrative issues, with little emphasis on the environment. KRI is facing serious environmental problems, yet these did not emerge as major concerns during the election campaign. This paper reviews the key issues raised during the KRI 2024 election by the major parties and establishes that the environment was sidelined. It highlights some environmental problems with a focus on pollution. It argues that the prioritisation of the issues was incorrect, and suggests that raising environmental awareness among the public is important for environmental problems to be tackled in the future.